Ganti Rugi Perbuatan Melawan Hukum dalam Gugatan Perwakilan Kelompok di Indonesia - Erna Widjajati (Jurnal Hukum IUS QUIA IUSTUM, 2011)
The problem reviewed in the research was the procedure of compensation on tort in representation claim. This research was juridical normative research. The legal material used in this research was primary legal material in the form of legislation and court decisions, and secondary legal material. The legal material was analyzed qualitatively. This research concluded that if the compensation claim was granted, the judge had decided the amount of compensation in detail, group determination, the mechanism of compensation distribution and steps must be taken by the group representative as well as the obligation to conduct the notification.Key words : Group representation claim, compensation, tort